Establishing a Clinically Relevant Large Animal Model Platform for TBI Therapy Development: Using Cyclosporin A as a Case Study. (May 2015) - Margulies, Susan S.; Kilbaugh, Todd; Sullivan, Sarah; Smith, Colin; Propert, Kathleen; Byro, Melissa; Saliga, Kristen; Costine, Beth A.; Duhaime, Ann‐Christine
Abstract: We have developed the first immature large animal translational treatment trial of a pharmacologic intervention for traumatic brain injury (TBI) in children. The preclinical trial design includes multiple doses of the intervention in two different injury types (focal and diffuse) to bracket the range seen in clinical injury and uses two post‐TBI delays to drug administration. Cyclosporin A (CsA) was used as a case study in our first implementation of the platform because of its success in multiple preclinical adult rodent TBI models and its current use in children for other indications. Tier 1 of the therapy development platform assessed the short‐term treatment efficacy after 24 h of agent administration. Positive responses to treatment were compared with injured controls using an objective effect threshold established prior to the study. Effective CsA doses were identified to study in Tier 2. In the Tier 2 paradigm, agent is administered in a porcine intensive care unit utilizing neurological monitoring and clinically relevant management strategies, and intervention efficacy is defined as improvement in longer term behavioral endpoints above untreated injured animals. In summary, this innovative large animal preclinical study design can be applied to future evaluations of other agents that promote recovery or repair after TBI.